Prediction of the morphology of polymer-clay nanocomposites. (February 2015) - Ceraulo, M.; Morreale, M.; Botta, L.; Mistretta, M.C.; Scaffaro, R.
Abstract: Polymer nanocomposites have continually attracted increasing interest over the last decade, due to significant improvements they can offer compared to neat polymer matrices. However, the final morphology of a nanocomposite, determined by several variables, can significantly influence the macroscopic properties of the final product. Therefore, it is important to study the interactions between processing, morphology, structure and rheological properties, and the suitability of existing models in order to predict the system's behaviour with change of the main processing variables. In this work, the applicability of a predictive theory based on the Wu model was formulated and proposed in order to predict the morphology of nanocomposite systems. This theory allows description of a polymer matrix - lamellar filler system, provided that the interactions between the two components and the processing are known. In particular, a lamellar filler has been considered as a deformable second component of a blend, with its behaviour depending on the processing and on the interactions with the polymer matrix. This allowed analyzing different behaviour for the systems, due to the different polarity of the matrix, which may lead to a classification of polymer nanocomposites in two or more families, according to their different matrix polarities.